Pengaruh Semangat Kerja Dan Disiplin Kerja Terhadap Kinerja Guru Di Smp Pawyatan Daha 1 - Mohammad Iqbal Abidin; Diana Ambarwati; Zaenul Muttaqien (Pusat Riset dan Inovasi Nasional, 2023)
This research aims to determine how significant the effect of morale and work discipline on teacher performance. This type of research uses a quantitative approach. The research sample was Pawyatan Daha 1 Middle School teachers with a total of 34 respondents. This study uses a saturated sample technique. The data collection technique uses a questionnaire that has been tested for validity and reliability first. This research data analysis technique uses multiple linear regression.